Tail dependence under sample failures - Ferreira, Marta Susana (2020)
When collecting samples, sometimes failures of observations occur and consequently missing data. This can have an impact on the analysis and subsequent inference, especially if the study focuses on the extreme values where the data is more scarce. In this work, we analyze the effect of different types of failures on the dependence within the tail of a stationary series. We will also present some examples.